Customer perceptions of rural banks in Ghana: a case study of selected companies in Ashanti region. - Acheampong, Kwame Yeboah (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Award Of The Degree Of Master Of Business Administration (Strategic Management And Consulting).